Ai-Generated Works and The Dilemma of Authorship: A Comparative Study of the Eu and New Zealand Copyright Regimes - Nidhi Dahiya; Prachi Goyal (Journal of Advanced Research in Journalism & Mass Communication, 2026)
Artificial intelligence has forced copyright law to confront questions it was never designed to answer. When a system produces a piece of music, an illustration, or a written text without traditional human creativity, it becomes unclear who, if anyone, should be treated as the author. This paper compares how the European Union and New Zealand address this issue through their distinct legal frameworks. The European Union holds firmly to the view that copyright protection requires human authorship. If a work contains no meaningful human creative input, it falls outside the copyright system entirely. New Zealand takes a more functional approach by recognising “computer-generated works” and assigning authorship to the person who made the arrangements for the work to be created. By examining legislation, case law and current policy discussions, this paper highlights the strengths and weaknesses of both models. While the EU’s approach protects the traditional human-centred foundation of copyright, it leaves many AI-generated works in a legal grey zone. New Zealand’s approach provides certainty and economic clarity but raises questions about how far authorship can be detached from human creativity. The comparison suggests that neither system offers a complete solution and that future policy will need to balance technological development with the core purpose of copyright.